Silica nanoparticles interfere with mast cell activation by enhancing intracellular Ca2+ levels and aggravate ovalbumin-mediated asthma - Jinhua Wei; Dongyuan Bian; Shijian Huang; Xiaobing Wu; Liu Yang; Shasha Li; Beibei Xia; Yanbo Li; Guimiao Lin (Hygiene and Environmental Health Advances)
Silica nanoparticles (SiNPs) exist widely in the environment. The likelihood of people being exposed to SiNPs has increased dramatically, and its biosafety bring a great concern. Mast cells are a type of key effector cells that mediate the occurrence of allergic reactions through IgE and non-IgE activation pathways.To date, the effects of SiNPs on these two activation pathways of mast cells remain unclear. In this study, RBL-2H3 cells and ovalbumin (OVA) asthma mice were used to investigate the effects of SiNPs on mast cell activation and its mediating asthma. in vitro studies, SiNPs significantly promoted the release of inflammatory factors TNF-α and IL-1β, but didn’t affect the release of β-Hex (degranulation) in the C48/80-mediated non-IgE activation pathway. In the IgE activation pathway, SiNPs significantly enhanced the release of TNF-α and IL-1β, and also promoted mast cell degranulation by increasing intracellular Ca2+ levels. in vivo study, respiratory exposure to SiNPs significantly enhanced the serum histamine and the levels of cytokines (IL-6, TNF-α and IL-1β) in bronchoalveolar lavage fluid (BALF) from asthmatic mice sensitized, thickened the airway walls, increased the inflammatory cells infiltration and the number of mast cells, suggesting that SiNPs significantly aggravated OVA-mediated asthma in mice. These findings reveal the effects of SiNPs on mast cells and their mediated allergic reactions, providing scientific clues for the prevention and treatment of allergic diseases, especially asthma.